Fast Changes in Seismic Attenuation of the Upper Crust due to Fracturing and Fluid Migration: The 2016–2017 Central Italy Seismic Sequence - Gabrielli, Simona; Akinci, Aybige; Ventura, Guido; Napolitano, Ferdinando; Del Pezzo, Edoardo; De Siena, Luca (Frontiers in Earth Science, 2022)
The Amatrice-Visso-Norcia seismic sequence struck Central Italy across the Apenninic normal faults system in 2016. Fluids likely triggered the sequence and reduced the stability of the fault network following the first earthquake (Amatrice, Mw6.0), with their migration nucleating the Visso (Mw5.9) and Norcia (Mw6.5) mainshocks. However, both spatial extent and mechanisms of fluid migration and diffusion through the network remain unclear. High fluid content, enhanced permeability and pervasive microcracking increase seismic attenuation, but different processes contribute to different attenuation mechanisms. Here, we measured and mapped peak delay time and coda attenuation, using them as proxies of seismic scattering and absorption before and during the sequence. We observed that the structural discontinuities and lithology control the scattering losses at all frequencies, with the highest scattering delineating carbonate formations within the Gran Sasso massif. The Monti Sibillini thrust marks the strongest contrasts in scattering, indicating a barrier for northward fracture propagation. Absorption does not show any sensitivity to the presence of these main geological structures. Before the sequence, low-frequency high-absorption anomalies distribute around the NW-SE-oriented Apennine Mountain chain. During the sequence, a high-absorption anomaly develops from SSE to NNW across the seismogenic zone but remains bounded north by the Monti Sibillini thrust. We attribute this spatial expansion to the deep migration of CO2-bearing fluids across the strike of the fault network from a deep source of trapped CO2 close to the Amatrice earthquake. Fluids expand SSE-NNW primarily during the Visso sequence, then diffuse across the fault zones during the Norcia sequence.